Expression of p21 in SV40 large T antigen positive human pleural mesothelioma: relationship with survival. Issue 4 (1st April 2002) - Baldi, A; Groeger, A M; Esposito, V; Cassandro, R; Tonini, G; Battista, T; Di Marino, M P; Vincenzi, B; Santini, M; Angelini, A; Rossiello, R; Baldi, F; et al.
Abstract : Background: Mesothelioma is the most commonly occurring primary pleural neoplasm. Several studies have documented an increase in the incidence of this malignancy during the last decades. Although the association between asbestos exposure and development of mesothelioma is generally accepted, the exact mechanism of carcinogenesis is unknown. Recently, Simian virus 40 large T antigen (SV40 Tag) expression has been detected in pleural mesothelioma. The ability of SV40 oncoproteins to inactivate p53 and retinoblastoma tumour suppressor proteins has been proposed as an important step in the pathogenesis of human mesothelioma. Methods: To obtain a better understanding of the molecular mechanisms of the pathogenesis of mesothelioma, the expression of the cell cycle inhibitor p21 WAF1/CIP1 (p21), a downstream target of p53, was evaluated immunohistochemically in a group of 29 mesothelioma specimens already characterised for the presence of SV40 Tag sequences. Results: Statistical analysis did not reveal any correlation between p21 expression and histopathological type of mesothelioma using the κ 2 test (p=0.577). A significant positive relationship was found between p21 expression level and the patients' overall survival according to the Kaplan-Meier survival curves and using a log rank test (median difference in survival 7 months, 95% CI 4.8 to 9.9; p<0.001). Conclusions: Determination of p21 expression bears a prognostic significance in patients affected with mesothelioma, further underlining the role of SV40 in the pathogenesis of malignant pleural mesothelioma.